Diagnosis, differential diagnosis and misdiagnosis of Susac syndrome. (25th March 2022) - Triplett, James D.; Qiu, Jessica; O'Brien, Billy; Gopinath, Sumana; Trewin, Benjamin; Spring, Penelope J.; Shaffi, Mohamed; Ip, Jerome; Chan, Fiona; Chen, Luke; Wilson, Ian; Muller, Claire; et al.
Abstract: Background and purpose: Susac syndrome (SuS) is an inflammatory condition of the brain, eye and ear. Diagnosis can be challenging, and misdiagnosis is common. Methods: This is a retrospective review of the medical records of 32 adult patients from an Australasian cohort of SuS patients. Results: An alternative diagnosis prior to SuS was made in 30 patients (94%) with seven patients receiving two or more diagnoses. The median time to diagnosis of SuS was 3 months (range 0.5–100 months). The commonest misdiagnoses were migraine in 10 patients (31%), cerebral vasculitis in six (19%), multiple sclerosis in five (16%) and stroke in five (16%). Twenty‐two patients were treated for alternative diagnoses, 10 of whom had further clinical manifestations prior to SuS diagnosis. At presentation seven patients (22%) met criteria for definite SuS, 19 (59%) for probable SuS and six (19%) for possible SuS. Six patients (19%) presented with brain–eye–ear involvement, 14 with brain–ear (44%), six with brain–eye (19%) and six (19%) with only brain involvement. In patients with the complete triad of symptoms the median delay to diagnosis was 3 months (range 1–9 months) compared to 5.25 months (range 0.5–100 months) for patients with encephalopathy and ocular symptoms at presentation. Conclusions: Susac syndrome patients are frequently misdiagnosed at initial presentation, despite many having symptoms or radiological features that are red flags for the diagnosis. Delayed diagnosis can lead to patient morbidity. The varied ways in which SuS can present, and clinician failure to consider or recognize SuS, appear to be the main factors leading to misdiagnosis. Abstract : The delay to diagnosis of Susac syndrome was influenced by extent of brain, eye and ear involvement at presentation with the fastest diagnosis in patients with brain only involvement, and the slowest diagnosis in those with brain and eye involvement.